Attenuation correction in CZT myocardial perfusion imaging comparison of supine-prone and low-dose CT-corrected supine acquisitions. Issue 8 (August 2021) - Hahn, Eva; Kammeier, Annett; Burchert, Wolfgang; Lindner, Oliver
Abstract : Aims: The study aimed to investigate whether additional prone imaging delivers comparable results to supine imaging with low-dose computed tomography (CT) attenuation correction (CTAC) in cadmium, zinc and telluride (CZT) myocardial perfusion imaging. Methods and results: Thirty-four patients with an indication for myocardial perfusion imaging were studied with a CZT camera in the supine and then prone position. Furthermore, a low-dose CT was acquired. Three data sets were reconstructed and considered for analysis: (1) supine CZT, (2) supine CZT with CTAC and (3) supine CZT with additional prone CZT. Based on 17-segment polartomograms, we compared radiopharmaceutical uptake percentage, summed stress score (SSS), summed rest score (SRS), summed difference score (SDS), total ischemic and scarred segments, and finally scan classification and clinical decision-making. SSS of supine/supine-CTAC/supine-prone was 341/229/253 ( P  < 0.05), SRS was 246/156/164 ( P  < 0.05) and SDS was 104/88/96 (ns), respectively. Total ischemic segments were 65/67/65 (ns) and total scarred segments 96/62/69 ( P  < 0.05), respectively. The frequency of normal scans was highest for supine-prone, followed by supine-CTAC and supine (41/35/24%, respectively). Supine imaging indicated 23% of patients for invasive coronary angiography, both supine-CTAC and supine-prone 18%. These two showed a significant intercorrelation. Conclusion: Additional prone imaging and CTAC are mainly correct for the amount and extent of myocardial scars. Both methods increase the frequency of normal scans and show a significant agreement in clinical decision-making. Additional prone imaging appears as a useful alternative when a low-dose CT for attenuation correction is not available.